Transformative Management Innovation in Islamic Education: Enhancing Institutional Adaptability, Efficiency, and Educational Relevance - Syarip Syarip; M. Sirozi; Mardiah Astuti (Dirasah International Journal of Islamic Studies, 2026)
Despite growing scholarly attention to management innovation in Islamic education, existing research remains theoretically fragmented, with limited integration of governance, leadership, curriculum, and technology into unified analytical frameworks. This systematic literature review (SLR) critically synthesizes and theorizes management innovation by identifying dimensions, analyzing interconnections, and proposing an integrated analytical framework. Following PRISMA 2020, we searched Scopus (2015–2025) using TITLE-ABS-KEY Boolean terms: ("Islamic education management" OR “madrasah management" OR “pesantren governance") AND ("innovation" OR "transformation” OR "reform"). Inclusion criteria: (i) peer-reviewed English-language studies; (ii) focus on management/governance/leadership innovation in Islamic institutions; (iii) explicit discussion of institutional outcomes; (iv) exclusion of non-institutional or theological studies. Two reviewers independently screened records. Quality appraisal used MMAT 2018—thematic synthesis employed Braun and Clarke’s (2006) reflexive approach. Of 151 records, 107 met the inclusion criteria. Only 34 studies (31.8%) employed explicit theoretical lenses, while 89 studies (83.2%) were confined to Indonesian contexts. Thematic analysis identified five interconnected dimensions: curriculum integration (n=42), transformative leadership (n=38), human resource professionalization (n=31), digital governance (n=27), and global-local curriculum alignment (n=35). Cross-dimensional analysis indicated that synergistic integration correlated with superior institutional adaptability. This review proposes the Integrated Management Innovation Framework for Islamic Education (IMIF-IE), theorizing management innovation as a multidimensional process in which five subsystems function as interdependent drivers of institutional outcomes. Future research should prioritize cross-national comparative designs, longitudinal outcome studies, theoretical integration with institutional theory, and digital governance ethics.